IMPLEMENTASI STRATEGI KEMITRAAN, DIFERENSIASI, DAN LAYANAN UNTUK MENINGKATAN KINERJA INDUSTRI KULINER DI KOTA DENPASAR - Anggraini, Felicia; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 4 No 11 (2015), 2015)
Every culinary industry requires the right competitive strategy for their companies to maximize their performance. Improving the performance of the company is not easy, it is necessary to make a consistent performance improvement on a sustainable basis. This research was conducted to know the effect of partnership, differentiation, and service strategies on the culinary industry performance improvement in Denpasar. This research was conducted in Denpasar City. The population used was a number of culinary companies in a micro and small scale, in the form of a restaurant that has been registered and has governmental permits. The sample taken was as many as 102 respondents with non-probability sampling methods, particularly purposive sampling method. The analysis technique used was multiple linear regressions. The results showed that each variable of partnership, differentiation, and the service strategies had a positive and significant impact on the performance improvement. This indicated that the implementation of the strategy of partnership, differentiation, and services in the culinary industry could improve the performance of the company.
Keywords: Partnership Strategy; Differentiation Strategy; Service Strategy; Performance Improvement